TINJAUAN HUKUM ISLAM TERHADAP EFISIENSI PEMBAYARAN ZAKAT SECARA ONLINE DI BAZNAS - Baharuddin; Sohrah (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2022)
Islam is present in the midst of a society that is so unique that it presents various kinds. Zakat is one of the practices of the five pillars of Islam which is an absolute obligation for all Muslim communities as stated in the texts of the Qur'an and Al-Hadith. Therefore, everyone is encouraged to become muzakki, where each muzakki plays a role in overcoming poverty, meaning that hope is aimed at people who are able and to the poor themselves. The main problem in this study is how the Efficiency of Online Zakat Payments Judging from Islamic Law at the National Amil Zakat Agency Kab. soppeng. This type of research is a